2014
DOI: 10.1038/srep04559
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles for the telomeric repeats in chromosomally integrated human herpesvirus-6

Abstract: Approximately 1 percent of healthy individuals carry human herpesvirus-6 within a host chromosome. This is referred to as chromosomally integrated herpesvirus-6 (CIHHV-6). In this study, we investigated the chromosomal integration site in six individuals harboring CIHHV-6B. Using FISH, we found that HHV-6B signals are consistently located at the telomeric region. The proximal endpoints of the integrated virus were mapped at one of two telomere-repeat-like sequences (TRSs) within the DR-R in all cases. In two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Even though the formal integration mechanism has yet to be demonstrated experimentally, sequencing of ciHHV-6A/B indicates that the TMR of the DR R of the genome is fused to the host chromosome telomeric repeats with loss of pac2 sequence from DR R . Such a structure is compatible with HR-mediated viral integration (5,30,31).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Even though the formal integration mechanism has yet to be demonstrated experimentally, sequencing of ciHHV-6A/B indicates that the TMR of the DR R of the genome is fused to the host chromosome telomeric repeats with loss of pac2 sequence from DR R . Such a structure is compatible with HR-mediated viral integration (5,30,31).…”
Section: Discussionmentioning
confidence: 69%
“…Analysis of the integrated virus genome revealed that the perfect TMR of the DR R region are fused to the host chromosome accompanied by a loss of the pac2 sequence, consistent with an integration mediated by HR between the viral TMR and the host telomere (5). At the other end of the viral genome, the pac1 region is also lost and additional telomeric repeats are added, suggesting that the TMR in DR L is a substrate for the generation of a new telomere (29)(30)(31).…”
mentioning
confidence: 93%
“…Upon cell replication and division, the 26-28 nucleotide pac1 sequences could erode until the TMR region is encountered. TMR could then serve as template for telomerase, as recently reported [33]. It remains unknown which cellular/viral proteins could participate in this BIR-dependent HHV-6 integration.…”
Section: Introductionmentioning
confidence: 88%
“…The integration occurs solely in telomeres and it has been shown that the telomeric sequences within the HHV-6A genome are essentials for efficient integration into chromosomes (4). Furthermore, the integrated virus has been sequenced and its orientation and missing sections are compatible with an integration by HR between the viral TMRs and the telomeres (11, 63, 64). Whether TRF2 plays a role in HHV-6A/B integrations remains to be shown.…”
Section: Discussionmentioning
confidence: 99%